2018
DOI: 10.1097/md.0000000000011412
|View full text |Cite
|
Sign up to set email alerts
|

Radiopathological characteristics and outcomes of phyllodes tumor of the breast in Malaysian women

Abstract: Phyllodes tumor or cystosarcoma phyllodes is a rare fibroepithelial neoplasm which arises from the periductal stroma of the breast. They are classified as benign, borderline, and malignant based on the histologic features. However, all phyllodes tumor (PT) subtypes are regarded as having malignant potential and correct diagnosis is important for surgical management and optimal care. This study is a retrospective review of 76 women diagnosed as PT with highlights on the imaging characteristics, pathology, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
(69 reference statements)
1
11
0
Order By: Relevance
“…However, according to a review involving 5,530 patients, the overall recurrence rate of these patients is high, at 19.1% ( 14 ). According to a study in the National Cancer Database of the Cancer Council of the American College of Surgeons, involving 3120 patients, adjuvant radiotherapy for phyllodes tumors was used in 19.5% of cases between 2008 and 2009 ( 9 ). Data from this large retrospective study showed that radiotherapy can prolong the time of local recurrence and reduce the rate of local recurrence, but it has no significant effect on survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, according to a review involving 5,530 patients, the overall recurrence rate of these patients is high, at 19.1% ( 14 ). According to a study in the National Cancer Database of the Cancer Council of the American College of Surgeons, involving 3120 patients, adjuvant radiotherapy for phyllodes tumors was used in 19.5% of cases between 2008 and 2009 ( 9 ). Data from this large retrospective study showed that radiotherapy can prolong the time of local recurrence and reduce the rate of local recurrence, but it has no significant effect on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the high recurrence rate, adjuvant radiotherapy as an improvement in local control has increased in the past few decades ( 8 , 9 ). In the only prospective study published so far, Mitus et al .…”
Section: Introductionmentioning
confidence: 99%
“…PTs are rare breast neoplasms characterized by rapid growth [1,7,8]. They usually appear in women between 35 and 55 years of age, with an average presentation at 45 years, occurring ten to 20 years after FA peak incidence, by contrast with this case, in which the patient manifested the disease before 25 years of age [[9], [10], [11], [12]]. On physical examination, PTs are usually rigid, well delimited, mobile, non-adherent to the skin, with an average size of 4–7 cm, as described previously [2,3,13].…”
Section: Discussionmentioning
confidence: 99%
“…Local recurrence rates are 3.6–8% for benign PT, 14% for borderline and 30–42% for malignant [1,4,13]. Although our patient presented with benign and borderline PTs, she had several recurrences, probably associated with compromised surgical margins, considered the main risk factor for recurrence [9,13,17,19]. Metastatic potential is also closely related to malignancy, with greater hematogenous spread, mainly pulmonary and bone, justifying systemic staging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation